1998
DOI: 10.1038/35318
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional preservation of algae and animal embryos in a Neoproterozoic phosphorite

Abstract: Phosphorites of the late Neoproterozoic (570 Ϯ 20 Myr BP) Doushantuo Formation, southern China, preserve an exceptional record of multicellular life from just before the Ediacaran radiation of macroscopic animals. Abundant thalli with cellular structures preserved in three-dimensional detail show that latest-Proterozoic algae already possessed many of the anatomical and reproductive features seen in the modern marine flora. Embryos preserved in early cleavage stages indicate that the divergence of lineages lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
378
1
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 713 publications
(397 citation statements)
references
References 25 publications
(20 reference statements)
13
378
1
5
Order By: Relevance
“…We are aware that our findings have also bearing on the ongoing discussion concerning the biological affinities of phosphatic microfossils from the Neoproterozoic (Ediacaran) Doushantuo Formation of south China described originally as post mortem phosphatized volvocalean-like green algae [44,45] or resting eggs and blastula embryos of early animals 8 [46,47,48,49,50] . Interestingly, these microfossils have recently been also interpreted as remnants of giant bacteria comparable to modern sulphur bacteria of the genus Thiomargarita [51,52] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware that our findings have also bearing on the ongoing discussion concerning the biological affinities of phosphatic microfossils from the Neoproterozoic (Ediacaran) Doushantuo Formation of south China described originally as post mortem phosphatized volvocalean-like green algae [44,45] or resting eggs and blastula embryos of early animals 8 [46,47,48,49,50] . Interestingly, these microfossils have recently been also interpreted as remnants of giant bacteria comparable to modern sulphur bacteria of the genus Thiomargarita [51,52] .…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion confirmed our earlier suggestion [4] that many acritarchs are unicellular green algae and that the internal bodies represent their asexual reproductive structures (spores). To our knowledge, the c. 420 Ma-old specimens shown in this report represent the earliest thus far described sporulating unicellular green algae (Chlorococcales).We are aware that our findings have also bearing on the ongoing discussion concerning the biological affinities of phosphatic microfossils from the Neoproterozoic (Ediacaran) Doushantuo Formation of south China described originally as post mortem phosphatized volvocalean-like green algae [44,45] or resting eggs and blastula embryos of early animals 8 [46,47,48,49,50] . Interestingly, these microfossils have recently been also interpreted as remnants of giant bacteria comparable to modern sulphur bacteria of the genus Thiomargarita [51,52] .…”
mentioning
confidence: 95%
“…Term acritarchs, which was applied to such organisms in referring to their uncertain origins, is now somewhat misleading because many of these microfossils have been progressively allocated to specific groupings, mainly eukaryotic phytoplankton (Tappan, 1980;Moczydłowska, 1991Moczydłowska, , 2011Colbath and Grenfell, 1995;Arouri et al, 1999Arouri et al, , 2000Talyzina and Moczydłowska, 2000;Wicander, 2002;Grey, 2005;Traverse, 2007;Molyneux, 2009;Kaźmierczak and Kremer, 2009;Moczydłowska et al, 2011). There are exceptions, such as microfossil Tianzhushania identified as a metazoan embryo (Xiao et al, 1998;Yin et al, 2004Yin et al, , 2007 or a holozoan protist (Huldtgren et al, 2011;Bengtson et al, 2012), and "Tappania" from the Wynniatt Formation as a fungus (Butterfield, 2005(Butterfield, , 2009Javaux 2007). Some unidentified Ediacaran taxa, together with Alicesphaeridium and Gyalosphaeridium, were claimed to be potential diapause egg cysts (Cohen et al, 2009), based on morphology but lacking the evidence of cell division (Moczydłowska et al, 2011).…”
Section: Biological Affinity Of Dictyosphaerashuiyousphaeridium Plexusmentioning
confidence: 99%
“…In Drosophila, genetic analyses have demonstrated that homeobox genes control embryonic segment number, polarity and identity (Akam 1987;Scott & Carroll 1987). The fossils of embryos identified in a Precambrian phosphate deposit in central Guizhou show that the body plans of these prototypes of bilateral eumetazoa are similar to those of extant marine invertebrate embryos (Xiao et al 1998). It has been suggested that marine invertebrate embryos inherited the original bilaterian body plan (Davidson et al 1995).…”
Section: Introductionmentioning
confidence: 99%